2000
DOI: 10.1177/009127000004001009
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Hemostatic Effect of Externally Applied Notoginseng and Notoginseng Total Saponins

Abstract: No effective hemostatic agents are available for external use. This project was conducted to evaluate the hemostatic effects of notoginseng using a hemorrhagic rat model. Rats (n = 40) were divided into four groups, and their tails were transected 5 mm from the tip. Group 1 received no treatment (control), while the other groups received external powder applied to the wound. Group 2 received placebo (flour), group 3 received ground notoginseng, and group 4 received a saponin extract of notoginseng. The total b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been used in China for 600 years, for treatment of various diseases. Traditionally, it has been used for its hemostatic and cardiovascular effects (to arrest internal and external bleeding, reduce swelling and pain, as well as to disperse blood clots, eliminate blood stasis and promote blood circulation) (Campbell et al, 2007;Sun et al, 2003;White et al, 2000;Zhou and Ke, 2000). PNS, known as the key active components from root Panax notoginseng (Kim et al, 2009;Ng, 2006), have been generally studied and found to possess many pharmacological effects, including resistance against cerebral infarction and ischemia by inhibiting apoptosis and expression of caspase-1 and caspase-3 (Yao and Li, 2001;Yao and Li, 2002), therapeutic effect on atherosclerosis by lowering serum lipid level and regulating expression of vascular cell differentiation antigen 40 and matrix metalloproteinase 9 (Wang et al, 2008).…”
Section: Description Of Panax Notoginsengmentioning
confidence: 99%
“…It has been used in China for 600 years, for treatment of various diseases. Traditionally, it has been used for its hemostatic and cardiovascular effects (to arrest internal and external bleeding, reduce swelling and pain, as well as to disperse blood clots, eliminate blood stasis and promote blood circulation) (Campbell et al, 2007;Sun et al, 2003;White et al, 2000;Zhou and Ke, 2000). PNS, known as the key active components from root Panax notoginseng (Kim et al, 2009;Ng, 2006), have been generally studied and found to possess many pharmacological effects, including resistance against cerebral infarction and ischemia by inhibiting apoptosis and expression of caspase-1 and caspase-3 (Yao and Li, 2001;Yao and Li, 2002), therapeutic effect on atherosclerosis by lowering serum lipid level and regulating expression of vascular cell differentiation antigen 40 and matrix metalloproteinase 9 (Wang et al, 2008).…”
Section: Description Of Panax Notoginsengmentioning
confidence: 99%